Calcium Silicate-based Sealer Extrusion into the Bifurcation of the Mandibular Canal: A Case Report with 36-Month Follow-up - Zargar, Nazanin; Soltaninejad, Fatemeh; Mirebeigi jamasbi, Seyed Sepehr (Journal of Dental School, 2024)
Objectives The final phase of root canal therapy involves the obturation of the root canal system to prevent bacterial leakage and ensure successful outcomes. However, during this process, there is a risk of sealer extrusion into vital structures such as the mandibular canal, which can lead to sensory changes like paresthesia. Case This report discussed a 40-year-old female case who presented with a crown fracture and a periapical lesion on her endodontically treated mandibular left second molar. During the retreatment, bioceramic sealer was extruded into the mandibular canal. Immediate radiographic evaluation and cone beam computed tomography confirmed the sealer’s presence within the sub-branches of the mandibular canal, though the main canal was unaffected. Conservative treatment with ibuprofen and dexamethasone resulted in pain relief and the patient did not experience any neurological deficits such as paresthesia. A 36-month follow-up revealed successful healing of the periapical lesion and absorption of the extruded sealer. Conclusion This case highlighted the importance of precise endodontic techniques to prevent sealer extrusion and demonstrated the potential of conservative management in cases of sealer extrusion into sub-branches of inferior alveolar nerve.